Hypoxia-Induced miR-210 Promotes Endothelial Cell Permeability and Angiogenesis via Exosomes in Pancreatic Ductal Adenocarcinoma. (25th November 2022) - Wu, Guo; Ding, Xiaojie; Quan, Gang; Xiong, Jianwei; Li, Qiang; Li, Zhonghu; Wang, Yaqin
Abstract : Background . Exosomes have been proven to play important diagnostic, regulatory, or communication roles in tumorigenesis, tumor progression, or metastasis; in recent studies, lots of molecules, including miRNAs, were found to be aberrantly expressed in tumor exosomes and were correlated with tumor development. However, studies about the expression, relationship, or control mechanisms of miRNAs in exosomes in pancreatic ductal adenocarcinoma (PDAC) are scarce and urgently needed. The aim of this article was to identify and investigate abnormally expressed miRNAs in PDAC exosomes in vivo and in vitro . Methods . Microarray studies were used to detect aberrantly expressed miRNAs in PDAC exosomes, and miR-210 expression in cells or exosomes was further analyzed by qRT-PCR. Bioinformatics analyses, dual-luciferase assays, WB, and other assays were utilized to explore the miRNA molecular mechanisms. The living cell coculture model and immunofluorescence analysis were employed to image the communication between PDAC cells and endothelial cells. Other biological experiments in the study include a real-time intravital imaging system, EdU, transwell, xenograft models, and so on. Results . miR-210 is significantly expressed in PDAC exosomes and malignant cells. High miR-210 significantly facilitated tumor angiogenesis, cell invasion, and proliferation in PDAC cells. Further mechanistic detection revealed that miR-210 negatively regulated EFNA3 expression and participated in the PI3K/AKT/VEGFA or Wnt/Β-catenin/RHOA pathways, thus promoting tumor angiogenesis and cellular permeability. PDAC cells promote endothelial angiogenesis or permeability via miR-210 transmission by tumor exosomes. Exosomal miR-210 promotes PDAC progression in vivo . Further detection of PDAC plasma exosomal miR-210 suggests that exosomal miR-210 expression was high and significantly associated with vascular invasion and TNM stage and was an independent risk factor for PDAC overall survival. Conclusions . PDAC cell-secreted exosomes could promote angiogenesis and cellular permeability of neighboring endothelial angiogenesis or permeability via miR-210 transmission. Exosomal miR-210 may play important roles in tumor biology and may be a useful prognostic marker in PDAC.